1999
DOI: 10.1677/joe.0.1600075
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal changes during parturition in heifers and goats are related to the phases and severity of labour

Abstract: Parturition is a natural event that involves stress and pain for the mother. We thus hypothesized that levels of stress hormones measured during parturition could reflect levels reached in response to severe discomfort and pain of other kinds as well. The aim of this study was therefore to determine whether plasma concentrations of cortisol, adrenaline, noradrenaline, -endorphin, met-enkephalin, vasopressin and oxytocin vary depending on the phase and severity of labour in dairy heifers (ten) and dairy goats (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
59
1
11

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 56 publications
8
59
1
11
Order By: Relevance
“…It is only during the last hour before expulsion that a more sustained hypoxia and acidosis develops, most probably as the result of a more permanent reduction in uterine blood flow. The latter is caused by hyperstimulation of uterine contractions, because plasma oxytocin reaches peak levels at this late stage of delivery (Hydbring et al 1999), and by involution of the now unoccupied distal part of the uterine horn. A recent study, using ultrasonic transit-time measurements of umbilical blood flow during second stage labour, demonstrated that in calves born with a jugular blood pH<7.2, umbilical blood flow significantly decreases at the end of the expulsive stage; blood flow in the umbilical arteries and vein even ceased completely during passage of the calf's head through the vulva (Bleul et al 2007).…”
Section: The Calf During and Immediately After Birthmentioning
confidence: 99%
“…It is only during the last hour before expulsion that a more sustained hypoxia and acidosis develops, most probably as the result of a more permanent reduction in uterine blood flow. The latter is caused by hyperstimulation of uterine contractions, because plasma oxytocin reaches peak levels at this late stage of delivery (Hydbring et al 1999), and by involution of the now unoccupied distal part of the uterine horn. A recent study, using ultrasonic transit-time measurements of umbilical blood flow during second stage labour, demonstrated that in calves born with a jugular blood pH<7.2, umbilical blood flow significantly decreases at the end of the expulsive stage; blood flow in the umbilical arteries and vein even ceased completely during passage of the calf's head through the vulva (Bleul et al 2007).…”
Section: The Calf During and Immediately After Birthmentioning
confidence: 99%
“…Königsson et al [26] reported that after dexamethasone-induced parturitions distinct peaks of cortisol were only seen in cows with retained foetal membranes. This might be due to some kind of stress due to prolonged or difficult calving as suggested by Hydbring et al [25], but might also be due to an effect of the retained foetal membranes per se. Cows delivering the placenta at normal time did not have any peaks of cortisol [26].…”
mentioning
confidence: 93%
“…The levels of cortisol in the maternal blood circulation are very high during the time of parturition [23]. These rising levels were reported to be related to the stress condition with labour [24,25]. Twin-bearing cows had significantly higher mean plasma cortisol levels on the day of parturition than the singleton cows [24].…”
mentioning
confidence: 99%
“…Labour is a natural event associated with pain. Apart from the hormones known to be directly involved in the birth process in goats, blood plasma vasopressin concentrations increase to high levels at the birth of the fi rst kid and then decline (Hydbring et al, 1999). The reason for this is not clear, but it was suggested that the high levels were correlated to the pain during the phase of cervical dilatation.…”
Section: Introductionmentioning
confidence: 99%